Client perceptions of satisfaction and value for money in the employment of architects on private house projects. (2016) - Frimpong, Samuel; Dansoh, Ayirebi
Clients' perceptions of the satisfaction and value for money in employing architects are a major factor influencing their architect-seeking behaviour. The purpose of this paper is to investigate clients' perceptions of satisfaction and value for money when employing architects on small private house projects in Ghana. Using phenomenological studies, two themes and eight sub-themes were uncovered: competence and capabilities (performance; age and experience; availability and accessibility; service quality) and cost of engagement (cost of fees; fee flexibility; fee standardisation; convenience). The findings indicate among other things that clients found engaging an architect to be a needlessly arduous and expensive venture. Clients felt architects needed to be employed only on dream house projects. Furthermore, clients found it difficult to guesstimate architects' fees prior to their engagement. The study reveals information that will improve architects' understanding of the nature of clients, ensuring successful client-architect collaborations on house projects.